Thinnings in the Young Teak Coppice Forests of Betul Division - Seth, V. K. (Indian Forester, 1958)
The paper describes how within the last ten years a sound and practicable technique of carrying out thinnings in naturally regenerated teak areas has been developed and how it is being applied to the forests of Betul Division. The technique adopted is the best suited to the conditions that obtain in the forests and the results obtained are most gratifying.